The Arabidopsis csb3 mutant reveals a regulatory link between salicylic acid-mediated disease resistance and the methyl-erythritol 4-phosphate pathway - Gil, Ma José; Coego, Alberto; Mauch-Mani, Brigitte; Jordá, Lucia; Vera Pablo (My University, 2005)
We report on constitutive subtilisin3 (csb3), an Arabidopsis mutant showing strikingly enhanced resistance to biotrophic pathogens. Epistasis analyses with pad4, sid2, eds5, NahG, npr1, dth9 and cpr1 mutants revealed that the enhanced resistance of csb3 plants requires intact salicylic acid (SA) synthesis and perception. CSB3 encodes a 1-hydroxy-2-methyl-2-butenyl 4-diphosphate synthase, the enzyme controlling the penultimate step of the biosynthesis of isopentenyl diphosphate via the 2-C-methyl-d-erythritol-4-phosphate (MEP) pathway in the chloroplast. CSB3 is expressed constitutively in healthy plants, and shows repression in response to bacterial infection. We also show the pharmacological complementation of the enhanced-resistance phenotype of csb3 plants with fosmidomycin, an inhibitor of the MEP pathway, and propose that CSB3 represents a point of metabolic convergence modulating the magnitude of SA-mediated disease resistance to biotrophic pathogens.
Keywords: plantdefense; PstDC3000; biotrophicpathogens; defenseresponse